Implementasi Teknologi Financial Dalam Qris Sebagai Sistem Pembayaran Digital Pada Sektor Umkm Di Kota Binjai - Siti Aisyah; Nia Andriani; Niken Rahmadyah; Deby Novriansyah; Amelia Putri; Elsa Mayori (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Increasing, resulting in several changes fo;;owed by technological devlopments in the industrial revolution. One form of progress in internet technology is the use of financial technology in payment systems where payment transaction methods are facilitated by the phenomenon of a cashless society or payments using electronic money. MSMEs also experience this impact which emphasizes the importance of internet use. QRIS is the latest innovation in digital payments, namely the Quick Response Code Indonesian standard. QRIS, which was intiated by Bank Indonesia, provides convenience intransactions anywhere and anytime. This study aims to find out how the implementation of financial technology in QRIS as a Digital Payment System in the MSME Sector in Binjai Cuty. This research uses qualitative descriptive method. Data collection techniques, namely using observation, interviews, documentation and literature studies which will be analyzed through the author’s observations to answer the formulation of the research that the researcherts conducted in order to socialize the implementation of the use of QRIS in several MSMEs in the city of Binjai, namely street vendors such as Dayana Ponsel, Seafood Meatball Traders, Takoyaki Kimono, Geprek Chicken Vendors Adek Sri who are in the city Binjai. Through the interview method of several respondents from street vendors, the results of the study proved that 20% of MSME actors already use the the payment system using QRIS, but 80% of MSME traders do not know what QRIS is. QRIS helps merchants (MSMEs) to make payments mor ppractical, fast and secure and with the convenience of these transactions people choose to shop and will indirectly increase income for MSME players.